Business Model Canvas (BMC)’s Concept for SMEs in East Jakarta - Ika Febrilia; Mohamad Rizan; Basrah Saidani (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Setting up and building a business is not an easy matter. Not a few who failed and eventually went bankrupt. It turns out that one of the reasons is due to lack of careful planning. One business model that is considered effective is the Business Model Canvas (BMC), which is a management strategy for planning business concepts, infrastructure and company finances and can be applied not only by start-up businesses, but also by existing businesses. But, unfortunately BMC is not widely known by SMEs players. Therefore, in this community service activity, socialization was carried out on the concept and application of BMC, with partners from the Sub-Department of Industry, Trade, Cooperatives, Small and Medium Enterprises, East Jakarta City Administration, as well as participants who are SMEs in East Jakarta. The socialization used the classical method, namely in the form of an explanation from the resource person through a presentation on the BMC concept followed by application in the form of a simulation/joint practice. The output of this activity is in the form of articles published in the Jurnal Pemberdayaan Masyarakat Madani (JPMM) indexed by Sinta 3.